A low-temperature sintered conductive silver paste and its preparation method and application

By using a combination of bisphenol A epoxy resin containing strong polar groups and silver powders in silver paste, the problem of insufficient adhesion and conductivity of existing silver paste is solved, and high shear strength and low cost are achieved low temperature sintering effect.

CN116779213BActive Publication Date: 2024-12-17SUZHOU GINET NEW MATERIAL TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202310763087.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-27
Publication Date
2024-12-17
Estimated Expiration
2043-06-27

AI Technical Summary

Technical Problem

The existing silver paste has defects in adhesion, conductivity and shear strength, especially the low adhesion leads to lower shear strength and high sintering temperature, making it difficult to control the cost.

Method used

Using a combination of bisphenol A epoxy resin containing strong polar groups, spherical silver powder, sheet silver powder and nano silver powder, through low-temperature sintering technology, polar groups are used to improve the reactivity and dispersion of silver powder, reduce pores, and enhance Adhesion strength and conductivity.

Benefits of technology

Low-temperature sintered silver paste with high shear strength and good adhesion is achieved, which reduces the melting temperature of silver powder, simplifies the process, reduces the cost, and improves the conductivity and adhesion ability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116779213B_ABST
    Figure CN116779213B_ABST
Patent Text Reader

Abstract

The invention discloses a low-temperature sintering silver paste and a preparation method and application thereof. The raw materials of the low-temperature sintering silver paste include, by weight percentage, 25-35% of spherical silver powder, 20-30% of flaky silver powder, 20-25% of nano silver powder and 6-10% of high molecular polymer. The high molecular polymer is a bisphenol A epoxy resin containing a strong polar group. The polar group can attract silver ions to migrate to the surface of the silver powder to improve the reaction activity of silver, and the covalent bonds formed with the silver powder reduce holes, thereby improving the shear strength of the silver paste and reducing the sintering temperature, so that the silver paste has excellent adhesion and conductive properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of semiconductor packaging materials, and in particular relates to a low-temperature sintered silver paste with high shear strength and adhesion, and a preparation method and application thereof. Background Art

[0002] Sintering technology uses high temperatures to cause atoms on the surface of a material to diffuse into each other, forming dense crystals. Low-temperature sintering technology typically reduces the sintering temperature by reducing the size of the sintered particles. Nanosilver powder, due to its unique nano-properties, offers a new approach to semiconductor chip packaging. Silver's melting point is 961°C, but when the particles reach the nanometer level, its melting point drops significantly to around 100°C. Therefore, low-temperature sintering can be used to interconnect electronic products or chips. After sintering, the melting point of the sintered layer returns to silver's normal melting point, allowing electronic products to operate normally at high temperatures. Silver also has excellent thermal and electrical conductivity and good chemical stability, making it the most promising interconnect material for third-generation semiconductor packaging.

[0003] However, the silver pastes prepared by the existing disclosed silver pastes and preparation methods still have certain defects in terms of adhesion, conductivity, shear strength, etc. For example, the invention patent with publication number CN116130143A, entitled "A High-Temperature Resistant Elastic Conductive Silver Paste and Its Preparation Method," discloses a high-temperature resistant elastic conductive silver paste and its preparation method. The specification discloses: A high-temperature resistant elastic conductive silver paste, in parts by weight, is composed of the following raw materials: 5-15 parts of modified epoxy resin, 0.5-9 parts of curing agent, 1-5 parts of epoxy resin mixture, 5-10 parts of diluent, 0.1-0.5 parts of silane coupling agent, 0.01-0.2 parts of curing accelerator, 0.01-0.5 parts of dispersant, 0.2-2 parts of thixotropic agent, and 70-90 parts of conductive filler. The silver paste prepared by this method has excellent high-temperature resistance, but the disadvantage is that the adhesion is low, so the shear strength is relatively low.

[0004] Patent publication number CN115635212A, entitled "A Silver Solder Paste, Its Preparation Method, and Application," discloses a silver solder paste, its preparation method, and application. The specification discloses a silver solder paste prepared from a silver-ammine complex solution and an aldehyde-based organic solvent (R1-CHO, where R1 is a hydrocarbon group), with the molar ratio of the silver-ammine complex solution to the aldehyde-based organic solvent being 1:1 to 1:5. The silver-ammine complex is prepared from a silver ketocarboxylate and an amino organic solvent, with the molar ratio of the silver ketocarboxylate to the amino organic solvent being 1:1 to 1:5. This patent demonstrates high shear strength due to the combination of the silver-ammine complex solution and the aldehyde-based organic solvent. However, the disadvantage is the high silver content after sintering, which can be cost-prohibitive.

[0005] A hybrid conductive silver paste for nanochip encapsulation is disclosed in a patent with publication number CN109979639A, entitled "A Hybrid Conductive Silver Paste for Nanochip Encapsulation." The specification discloses: A hybrid conductive silver paste for nanochip encapsulation, which comprises, by weight percentage, 65%-85% silver powder, 5%-25% organic solvent, 1%-2% dispersant, 10%-20% organic vehicle, 0.5%-5% surfactant, and 0.1%-5% diluent. However, the sintering temperature of the silver paste is relatively high. Summary of the Invention

[0006] The purpose of the present invention is to address the deficiencies of the prior art, improve the adhesion and shear strength of the slurry by reducing holes, and provide a low-temperature sintered conductive silver paste with high shear strength and good adhesion, as well as a preparation method and application thereof.

[0007] To achieve the above-mentioned object, the present invention proposes the following technical solution: A low-temperature sintering silver paste comprises the following raw materials calculated by weight percentage:

[0008] Spherical silver powder: 25-35%;

[0009] Flake silver powder: 20-30%;

[0010] Nano silver powder: 20-25%;

[0011] High molecular weight polymer: 6-10%;

[0012] Solvent: 3-20%;

[0013] Other additives: 0.5-5%;

[0014] Wherein, the high molecular polymer is a bisphenol A epoxy resin containing polar groups.

[0015] Preferably, the particle size of the spherical silver powder is in the range of 1 to 20 μm, and the particle size of the flaky silver powder is in the range of 1 to 20 μm.

[0016] Preferably, the particle size of the nano silver powder is in the range of 50-500 nm.

[0017] Preferably, the structure of the bisphenol A epoxy resin containing polar groups is:

[0018]

[0019] Wherein, X- is Cl-, Br-, HS-, H2N-, RHN- or R2N-, preferably bisphenol A epoxy resin containing HS-.

[0020] Preferably, the solvent is selected from one or more of terpineol, turpentine, butyl carbitol, benzyl alcohol, ethanol, cyclohexanone, acetic acid, acetone, butanone, and n-butyl acetate.

[0021] Preferably, the other additives include a curing agent, a dispersant, an anti-settling agent and a leveling agent, which are used to achieve curing of the resin during heating and to improve the dispersibility and leveling properties of the slurry.

[0022] The present invention also provides a method for preparing a low-temperature sintered silver paste, comprising the following preparation steps:

[0023] S1, mixing the polymer, solvent and other additives in proportion and stirring to obtain an organic phase mixture;

[0024] S2, mixing the spherical silver powder, flaky silver powder and nano silver powder with the organic phase mixture in proportion and stirring to obtain a semi-finished product slurry;

[0025] S3, grinding the semi-finished product slurry to obtain a roller-milled mixture semi-finished product slurry;

[0026] S4. Degassing the semi-finished mixture slurry to obtain a low-temperature sintering silver paste.

[0027] Preferably, the stirring temperature in step S1 is room temperature, the rotation speed is 500-1000 rpm, and the stirring time is 15-20 min.

[0028] Preferably, the stirring temperature in step S2 is 25-30° C., the rotation speed is 300-500 rpm, and the stirring time is 5-10 min.

[0029] The invention also proposes an application of low-temperature sintering silver paste in semiconductor packaging.

[0030] During the curing process of the low-temperature sintering silver paste of the present invention, under the action of the polar group bisphenol A epoxy resin polymer, solvent, and catalyst, when two nanoparticles come into contact, a concave surface is generated in the "neck" region between the two particles, reducing the surface pressure in this region. Atoms diffuse from the convex surface region with positive curvature to the concave surface region with negative curvature, resulting in the aggregation of the two nanoparticles and the disappearance of the sintering neck region. Nanosilver paste utilizes the small size effect of nanosilver particles and, through the mutual diffusion of atoms between the nanosilver particles and the interconnecting material, is sintered at a temperature much lower than that of traditional powder metallurgy sintering, achieving interconnection between chips or components and substrates.

[0031] Furthermore, since no pressure is applied during sintering and the sintering temperature is low, nano-scale or submicron-scale pores are evenly distributed in the internal structure of the nano-silver paste interconnect, and obvious holes appear at the bottom in contact with the substrate. Too many holes will lead to insufficient adhesion. During the resin curing and shrinkage process, the silver nanoparticles will be subjected to a certain amount of extrusion. Under the action of extrusion, the particles that were originally in contact with each other will undergo a certain deformation, resulting in an increase in the contact area, thereby reducing the contact resistance; on the other hand, silver powders of different morphologies that are far away from each other will approach each other, greatly increasing the probability of a tunnel effect.

[0032] During the curing process of bisphenol A epoxy resin with polar groups, the polar groups can polarize the atoms on the silver surface, increase the reactivity of silver, thereby reducing the melting temperature of silver powder and achieving low-temperature sintering; and the covalent bonds formed with silver powder also chemically bond the silver filler to the resin network structure, which can improve the dispersion and bonding strength of silver, enhance the interaction between silver and the resin matrix, increase the contact area between silver powders, and reduce the gaps generated by nano-silver powder.

[0033] Compared with the prior art, the present invention has the following beneficial effects:

[0034] 1. This invention utilizes a bisphenol A epoxy resin containing strong polar groups. These special strong polar groups attract silver ions to the surface of the silver powder, forming a good bond with the silver powder, thereby increasing the reactivity of the silver, thereby reducing voids, improving bond strength, and lowering the melting temperature of the silver powder, achieving low-temperature sintering. Furthermore, the polar groups bind to the silver powder, reducing the formation of pores during the sintering process of the nano-silver powder.

[0035] 2. The preparation method of the present invention has a simple process, pressureless sintering, low sintering temperature, and does not require the addition of additional steps or pressure to obtain excellent adhesion and conductive properties.

[0036] 3. The main components of the present invention are a mixture of flaky silver powder, spherical silver powder and nano silver powder, which has lower cost than pure nano silver powder. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 is a scanning electron microscope image of a cross section of a bisphenol A epoxy resin silver paste with polar groups after sintering in an embodiment of the present invention;

[0038] Figure 2 This is a scanning electron microscope image of the cross section of the bisphenol A epoxy resin silver paste without polar groups after sintering in the comparative example of the present invention. DETAILED DESCRIPTION

[0039] The specific embodiments of the present invention are described in detail below with reference to the accompanying drawings, but it should be understood that the protection scope of the present invention is not limited by the specific embodiments.

[0040] Unless expressly stated otherwise, throughout the specification and claims, the term "comprise" or variations such as "include" or "comprising", etc., will be understood to include the stated elements or components but not to exclude other elements or components.

[0041] The present invention will be described in detail below with reference to the specific embodiments shown in the accompanying drawings. However, these embodiments do not limit the present invention, and any structural, methodological, or functional changes made by those skilled in the art based on these embodiments are all within the scope of protection of the present invention.

[0042] Example 1

[0043] Take 25g of spherical silver powder with a D50 of 5μm, 30g of flaky silver powder with a D50 of 10μm, 25g of nanopowder with a particle size of 50-500nm, 10g of HS-bisphenol A epoxy resin, 5g of solvent, and 5g of other additives, and prepare a low-temperature sintered conductive silver paste according to the following steps:

[0044] S1. 10 g of HS-bisphenol A epoxy resin, 5 g of solvent, and 5 g of other additives were mixed according to the component proportions and mechanically stirred at a stirring temperature of 25° C., a speed of 500 rpm, and a stirring time of 20 min to obtain an organic phase mixture;

[0045] S2, 25g of the spherical silver powder with a D50 of 5 μm, 30g of the flaky silver powder with a D50 of 10 μm, 25g of the nanopowder with a particle size of 50 to 500 nm and the organic phase mixture were mixed and mechanically stirred in proportion at a stirring temperature of 25°C, a speed of 500 rpm, and a stirring time of 5 min to obtain a semi-finished product slurry;

[0046] S3, grinding the semi-finished product slurry with a three-roll mill at a roller mill speed of 200 rpm / min, and filtering with a 400-mesh screen to obtain a roller-milled mixture semi-finished product slurry;

[0047] S4. Place the slurry with a viscosity of 60 Pa·s into a vacuum degassing machine for degassing to obtain a low-temperature pressureless sintering silver paste.

[0048] The scanning electron microscope image of the cross section of the conductive silver paste prepared by the above method after sintering is as follows: Figure 1 As shown, the conductive silver paste can be coated on a glass substrate to test its electrical properties. The specific method is: using a two-terminal resistor to measure its resistance R, measure the actual length L and cross-sectional area S of the coated sample, and according to the volume resistivity formula: The actual volume resistivity is calculated to be 8.8E-06Ω.cm.

[0049] The silver paste prepared by the above method was dispensed using a dispensing machine and then subjected to push-pull force testing using a universal tensile testing machine. Based on the push force (N), the bonding area (S), and the shear strength (N / S), the shear strength was calculated to be 15 MPa. The addition of bisphenol A epoxy resin containing polar groups to the conductive silver paste in this embodiment resulted in a paste with low resistance and high shear strength.

[0050] Example 2

[0051] Take 25g of spherical silver powder with a D50 of 5μm, 30g of flaky silver powder with a D50 of 10μm, 25g of nanopowder with a particle size of 50-500nm, 10g of Cl-bisphenol A epoxy resin, 7g of solvent, and 3g of other additives, and prepare a low-temperature sintered conductive silver paste according to the following steps:

[0052] S1. Mix 10 g of Cl-bisphenol A epoxy resin, 7 g of solvent, and 3 g of other additives in proportion and mechanically stir at a stirring temperature of 25° C., a speed of 500 rpm, and a stirring time of 20 min to obtain an organic phase mixture;

[0053] S2, 25g of the spherical silver powder with a D50 of 5 μm, 30g of the flaky silver powder with a D50 of 10 μm, 25g of the nanopowder with a particle size of 50 to 500 nm and the organic phase mixture were mixed and mechanically stirred in a certain mass ratio at a stirring temperature of 25°C, a speed of 500 rpm, and a stirring time of 5 min to obtain a semi-finished product slurry;

[0054] S3, grinding the semi-finished product slurry with a three-roll mill at a roller mill speed of 200 rpm / min, and filtering with a 400-mesh screen to obtain a roller-milled mixture semi-finished product slurry;

[0055] S4. Place the slurry with a viscosity of 60 Pa·s into a vacuum degassing machine for degassing to obtain a low-temperature pressureless sintering silver paste.

[0056] The conductive silver paste prepared by the above method can be coated on a glass substrate to test the electrical properties. The volume resistivity is calculated using the same method as in Example 1, and the actual volume resistivity is calculated to be 9.2E-06Ω.cm.

[0057] At the same time, the silver paste obtained by the above method was dispensed with a dispensing machine and then tested for push and pull strength using a universal tensile testing machine. The shear strength was calculated using the same shear strength calculation method as in Example 1, and the calculated shear strength was 13 MPa. Due to the addition of bisphenol A epoxy resin containing polar groups to the conductive silver paste of this embodiment, a paste with low resistance and high shear strength was obtained.

[0058] Example 3

[0059] Take 30g of spherical silver powder with a D50 of 5μm, 25g of flake silver powder with a D50 of 10μm, 25g of nanopowder with a particle size of 50-500nm, 8g of Br-bisphenol A epoxy resin, 10g of solvent, and 2g of other additives, and prepare a low-temperature sintered conductive silver paste according to the following steps:

[0060] S1. 8 g of Br-bisphenol A epoxy resin, 10 g of solvent, and 5 g of other additives were mixed in proportion and mechanically stirred at a stirring temperature of 25° C., a rotation speed of 500 rpm, and a stirring time of 20 min to obtain an organic phase mixture;

[0061] S2, 30g of the spherical silver powder with a D50 of 5μm, 25g of the flaky silver powder with a D50 of 10μm, and 25g of the nanopowder with a particle size of 50-500nm were mixed with the organic phase in a certain mass ratio and mechanically stirred at a stirring temperature of 25°C, a speed of 500rpm, and a stirring time of 5min to obtain a semi-finished product slurry;

[0062] S3, grinding the semi-finished product slurry with a three-roll mill at a roller mill speed of 200 rpm / min, and filtering with a 400-mesh screen to obtain a roller-milled mixture semi-finished product slurry;

[0063] S4. Place the slurry with a viscosity of 60 Pa·s into a vacuum degassing machine for degassing to obtain a low-temperature pressureless sintering silver paste.

[0064] The conductive silver paste prepared in the above manner can be coated on a glass substrate to test its electrical properties. The volume resistivity is calculated using the same method as in Example 1, and the actual volume resistivity is calculated to be 9.8E-06Ω.cm.

[0065] The silver paste obtained in the above manner was dispensed using a dispensing machine and then subjected to push-pull force testing using a universal tensile testing machine. The shear strength was calculated using the same method as in Example 1, yielding a shear strength of 12 MPa. In this example, the addition of a bisphenol A epoxy resin containing polar groups resulted in a paste with low resistance and high shear strength.

[0066] Example 4

[0067] Take 30g of spherical silver powder with a D50 of 5μm, 25g of flake silver powder with a D50 of 10μm, 25g of nanopowder with a particle size of 50-500nm, 8g of H2N-bisphenol A epoxy resin, 10g of solvent, and 2g of other additives, and prepare a low-temperature sintered conductive silver paste according to the following steps:

[0068] S1. 8 g of H2N-bisphenol A epoxy resin, 10 g of solvent, and 5 g of other additives were mixed in proportion and mechanically stirred at a stirring temperature of 25° C., a rotation speed of 500 rpm, and a stirring time of 20 min to obtain an organic phase mixture;

[0069] S2, 30g of the spherical silver powder with a D50 of 5μm, 25g of the flaky silver powder with a D50 of 10μm, and 25g of the nanopowder with a particle size of 50-500nm were mixed with the organic phase in a certain mass ratio and mechanically stirred at a stirring temperature of 25°C, a speed of 500rpm, and a stirring time of 5min to obtain a semi-finished product slurry;

[0070] S3, grinding the semi-finished product slurry with a three-roll mill at a roller mill speed of 200 rpm / min, and filtering with a 400-mesh screen to obtain a roller-milled mixture semi-finished product slurry;

[0071] S4. Place the slurry with a viscosity of 60 Pa·s into a vacuum degassing machine for degassing to obtain a low-temperature pressureless sintering silver paste.

[0072] The conductive silver paste prepared by the above method can be coated on a glass substrate to test the electrical properties. The volume resistivity is calculated using the same method as in Example 1, and the actual volume resistivity is calculated to be 9.5E-06Ω.cm.

[0073] The silver paste obtained in the above manner was dispensed using a dispensing machine and then subjected to push-pull force testing using a universal tensile testing machine. The shear strength was calculated using the same method as in Example 1, yielding a shear strength of 13 MPa. In this example, the addition of a bisphenol A epoxy resin containing polar groups resulted in a paste with low resistance and high shear strength.

[0074] Example 5

[0075] 35 g of spherical silver powder with a D50 of 5 μm, 20 g of flaky silver powder with a D50 of 10 μm, 20 g of nanopowder with a particle size of 50 to 500 nm, 6 g of RHN-bisphenol A epoxy resin, 18.5 g of solvent, and 0.5 g of other additives were used to prepare a low-temperature sintered conductive silver paste according to the following steps:

[0076] S1. 6 g of RHN-bisphenol A epoxy resin, 18.5 g of solvent, and 0.5 g of other additive components were mixed in proportion and mechanically stirred at a stirring temperature of 25° C., a rotation speed of 500 rpm, and a stirring time of 20 min to obtain an organic phase mixture;

[0077] S2, 35g of the spherical silver powder with a D50 of 5μm, 20g of the flaky silver powder with a D50 of 10μm, and 20g of the nanopowder with a particle size of 50-500nm were mixed with the organic phase in a certain mass ratio and mechanically stirred at a stirring temperature of 25°C, a speed of 500rpm, and a stirring time of 5min to obtain a semi-finished product slurry;

[0078] S3, grinding the semi-finished product slurry with a three-roll mill at a roller mill speed of 200 rpm / min, and filtering with a 400-mesh screen to obtain a roller-milled mixture semi-finished product slurry;

[0079] S4. Place the slurry with a viscosity of 60 Pa·s into a vacuum degassing machine for degassing to obtain a low-temperature pressureless sintering silver paste.

[0080] The conductive silver paste prepared in the above manner can be coated on a glass substrate to test its electrical properties. The volume resistivity is calculated using the same method as in Example 1, and the actual volume resistivity is calculated to be 10.1E-06Ω.cm.

[0081] The silver paste obtained in the above manner was dispensed using a dispensing machine and then subjected to push-pull force testing using a universal tensile testing machine. The shear strength was calculated using the same method as in Example 1, yielding a shear strength of 12 MPa. In this example, the addition of a bisphenol A epoxy resin containing polar groups resulted in a paste with low resistance and high shear strength.

[0082] Example 6

[0083] 35g of spherical silver powder with a D50 of 5μm, 20g of flaky silver powder with a D50 of 10μm, 20g of nanopowder with a particle size of 50-500nm, 6g of R2N-bisphenol A epoxy resin, 18.5g of solvent, and 0.5g of other additives were taken to prepare a low-temperature sintered conductive silver paste according to the following steps:

[0084] S1. Mix 6 g of R2N-bisphenol A epoxy resin, 18.5 g of solvent, and 0.5 g of other additives in proportion and mechanically stir at a stirring temperature of 25° C., a rotation speed of 500 rpm, and a stirring time of 20 min to obtain an organic phase mixture;

[0085] S2, 35g of the spherical silver powder with a D50 of 5μm, 20g of the flaky silver powder with a D50 of 10μm, and 20g of the nanopowder with a particle size of 50-500nm were mixed with the organic phase in a certain mass ratio and mechanically stirred at a stirring temperature of 25°C, a speed of 500rpm, and a stirring time of 5min to obtain a semi-finished product slurry;

[0086] S3, grinding the semi-finished product slurry with a three-roll mill at a roller mill speed of 200 rpm / min, and filtering with a 400-mesh screen to obtain a roller-milled mixture semi-finished product slurry;

[0087] S4. Place the slurry with a viscosity of 60 Pa·s into a vacuum degassing machine for degassing to obtain a low-temperature pressureless sintering silver paste.

[0088] The conductive silver paste prepared in the above manner can be coated on a glass substrate to test its electrical properties. The volume resistivity is calculated using the same method as in Example 1, and the actual volume resistivity is calculated to be 9.4E-06 Ω.cm.

[0089] The silver paste obtained in the above manner was dispensed using a dispensing machine and then subjected to push-pull force testing using a universal tensile testing machine. The shear strength was calculated using the same method as in Example 1, yielding a shear strength of 13 MPa. In this example, the addition of a bisphenol A epoxy resin containing polar groups resulted in a paste with low resistance and high shear strength.

[0090] Comparative Example 1

[0091] S1. Mix 1 g of HS-bisphenol A epoxy resin, 16 g of solvent, and 3 g of other additive components in proportion and mechanically stir at a stirring temperature of 25° C., a rotation speed of 500 rpm, and a stirring time of 20 min to obtain an organic phase mixture;

[0092] S2, 25g of the spherical silver powder with a D50 of 5μm, 30g of the flaky silver powder with a D50 of 10μm, 25g of the nanopowder with a particle size of 50-500nm and the organic phase were mixed and mechanically stirred in a certain mass ratio at a stirring temperature of 25°C, a speed of 500rpm, and a stirring time of 5min to obtain a semi-finished product slurry;

[0093] S3, grinding the semi-finished product slurry with a three-roll mill at a roller mill speed of 200 rpm / min, and filtering with a 400-mesh screen to obtain a roller-milled mixture semi-finished product slurry;

[0094] S4. Place the slurry with a viscosity of 60 Pa·s into a vacuum degassing machine for degassing to obtain a low-temperature pressureless sintering silver paste.

[0095] The conductive silver paste prepared in the above manner can be coated on a glass substrate to test its electrical properties. The volume resistivity is calculated using the same method as in Example 1, and the actual volume resistivity is calculated to be 20.5E-06Ω.cm.

[0096] The silver paste obtained in the above manner was dispensed using a dispensing machine and then subjected to push-pull force testing using a universal tensile testing machine. The shear strength was calculated using the same method as in Example 1, resulting in a shear strength of 4 MPa. Due to the low amount of bisphenol A epoxy resin containing polar groups added in this example, the resulting paste had higher resistance and lower shear strength.

[0097] Comparative Example 2

[0098] S1. Mix 12 g of HS-bisphenol A epoxy resin, 5 g of solvent, and 3 g of other additives in proportion and mechanically stir at a stirring temperature of 25° C., a rotation speed of 500 rpm, and a stirring time of 20 min to obtain an organic phase mixture;

[0099] S2, 25g of the spherical silver powder with a D50 of 5μm, 30g of the flaky silver powder with a D50 of 10μm, 25g of the nanopowder with a particle size of 50-500nm and the organic phase were mixed and mechanically stirred in a certain mass ratio at a stirring temperature of 25°C, a speed of 500rpm, and a stirring time of 5min to obtain a semi-finished product slurry;

[0100] S3, grinding the semi-finished product slurry with a three-roll mill at a roller mill speed of 200 rpm / min, and filtering with a 400-mesh screen to obtain a roller-milled mixture semi-finished product slurry;

[0101] S4. Place the slurry with a viscosity of 70 Pa·s into a vacuum degassing machine for degassing to obtain a low-temperature pressureless sintering silver paste.

[0102] The conductive silver paste prepared in the above manner can be coated on a glass substrate to test its electrical properties. The volume resistivity is calculated using the same method as in Example 1, and the actual volume resistivity is calculated to be 12.6E-06Ω.cm.

[0103] After the silver paste was dispensed using a dispensing machine, push-pull strength tests were performed using a universal tensile testing machine. The shear strength was calculated using the same method as in Example 1, resulting in a shear strength of 5 MPa. Due to the excessive addition of bisphenol A epoxy resin containing polar groups in this example, the resulting paste had higher resistance and lower shear strength.

[0104] Comparative Example 3

[0105] S1. Mix 4 g of HS-bisphenol A epoxy resin, 11 g of solvent, and 5 g of other additives in proportion and mechanically stir at a stirring temperature of 25° C., a rotation speed of 500 rpm, and a stirring time of 20 min to obtain an organic phase mixture;

[0106] S2, 25g of the spherical silver powder with a D50 of 5μm, 30g of the flaky silver powder with a D50 of 10μm, 25g of the nanopowder with a particle size of 50-500nm and the organic phase were mixed and mechanically stirred in a certain mass ratio at a stirring temperature of 25°C, a speed of 500rpm, and a stirring time of 5min to obtain a semi-finished product slurry;

[0107] S3, grinding the semi-finished product slurry with a three-roll mill at a roller mill speed of 200 rpm / min, and filtering with a 400-mesh screen to obtain a roller-milled mixture semi-finished product slurry;

[0108] S4. Place the slurry with a viscosity of 60 Pa·s into a vacuum degassing machine for degassing to obtain a low-temperature pressureless sintering silver paste.

[0109] The conductive silver paste prepared in the above manner can be coated on a glass substrate to test its electrical properties. The volume resistivity is calculated using the same method as in Example 1, and the actual volume resistivity is calculated to be 11.4E-06Ω.cm.

[0110] After the silver paste was dispensed using a dispensing machine, a push-pull test was performed using a universal tensile testing machine. The shear strength was calculated using the same method as in Example 1, resulting in a shear strength of 7 MPa. In this example, due to the addition of less bisphenol A epoxy resin containing polar groups, the resulting paste had higher resistance and lower shear strength.

[0111] Comparative Example 4

[0112] S1. Mix 10 g of bisphenol A epoxy resin without polar groups with 5 g of solvent and 5 g of other additives in proportion and stir mechanically at a stirring temperature of 25° C. and a speed of 500 rpm for 20 min to obtain an organic phase mixture;

[0113] S2, 25g of the spherical silver powder with a D50 of 5μm, 30g of the flaky silver powder with a D50 of 10μm, 25g of the nanopowder with a particle size of 50-500nm and the organic phase were mixed and mechanically stirred in a certain mass ratio at a stirring temperature of 25°C, a speed of 500rpm, and a stirring time of 5min to obtain a semi-finished product slurry;

[0114] S3, grinding the semi-finished product slurry with a three-roll mill at a roller mill speed of 200 rpm / min, and filtering with a 400-mesh screen to obtain a roller-milled mixture semi-finished product slurry;

[0115] S4. Place the slurry with a viscosity of 60 Pa·s into a vacuum degassing machine for degassing to obtain a low-temperature pressureless sintering silver paste.

[0116] The scanning electron microscope image of the cross section of the conductive silver paste prepared by the above method after sintering is as follows: Figure 2As shown, the conductive silver paste can be coated on a glass substrate to test the electrical properties. The volume resistivity is calculated using the same method as in Example 1, and the actual volume resistivity is calculated to be 13.6E-06Ω.cm.

[0117] The silver paste obtained in the above manner was dispensed with a dispensing machine and then tested for push-pull force using a universal tensile testing machine. The shear strength was calculated using the same method as in Example 1, and the calculated shear strength was 6 MPa. Since no bisphenol A epoxy resin containing polar groups was added to this embodiment, the resulting slurry had a higher resistance and a lower shear strength.

[0118] The description of specific exemplary embodiments of the present invention is for the purpose of illustration and description. These descriptions are not intended to limit the invention to the precise form disclosed, and it is apparent that many changes and variations are possible in light of the above teachings. The exemplary embodiments are selected and described for the purpose of explaining the specific principles of the invention and their practical application, thereby enabling those skilled in the art to make and utilize the various exemplary embodiments of the invention and various options and variations. The scope of the invention is intended to be defined by the claims and their equivalents.

Claims

1. A low temperature sintering silver paste, characterized in that: The invention comprises the following raw materials in percentage by weight: Spherical silver powder: 25-35%; Flake silver powder: 20-30%; Nano silver powder: 20-25%; High molecular weight polymer: 6-10%; Solvent: 3-20%; Other additives: 0.5-5%; Wherein, the high molecular polymer is a bisphenol A epoxy resin containing polar groups, and the structure is: Wherein, X- is Cl-, Br-, HS-, H2N-, RHN- or R2N-.

2. The low temperature sintering silver paste according to claim 1, characterized in that: The particle size of the spherical silver powder is in the range of 1 to 20 μm, and the particle size of the flaky silver powder is in the range of 1 to 20 μm.

3. The low temperature sintering silver paste according to claim 1, characterized in that: The particle size of the nano silver powder is in the range of 50-500 nm.

4. The low temperature sintering silver paste according to claim 1, characterized in that: The solvent is selected from one or more of terpineol, turpentine, butyl carbitol, benzyl alcohol, ethanol, cyclohexanone, acetic acid, acetone, butanone, and n-butyl acetate.

5. The low temperature sintering silver paste according to claim 1, characterized in that: The other additives include a curing agent, a dispersant, an anti-settling agent and a leveling agent, which are used to achieve curing of the resin during heating and to improve the dispersibility and leveling properties of the slurry.

6. A method for preparing a low-temperature sintering silver paste according to any one of claims 1 to 5, characterized in that: The method comprises the following preparation steps: S1, mixing and stirring the high molecular polymer, solvent and other additives in proportion to obtain an organic phase mixture; S2, mixing the spherical silver powder, flaky silver powder and nano silver powder with the organic phase mixture in proportion and stirring to obtain a semi-finished product slurry; S3, grinding the semi-finished product slurry to obtain a roller milled mixture semi-finished product slurry; S4, degassing the semi-finished mixture slurry to obtain low-temperature sintering silver paste.

7. The method for preparing low-temperature sintering silver paste according to claim 6, characterized in that: The stirring temperature in step S1 is room temperature, the rotation speed is 500-1000 rpm, and the stirring time is 15-20 min.

8. The method for preparing low-temperature sintering silver paste according to claim 6, characterized in that: The stirring temperature in step S2 is 25-30° C., the rotation speed is 300-500 rpm, and the stirring time is 5-10 min.

9. Use of the low-temperature sintering silver paste according to any one of claims 1 to 5 in semiconductor packaging.

Citation Information

Patent Citations

  • Mixed conductive silver paste for package of nano chip

    CN109979639A

  • Silver soldering paste and preparation method and application thereof

    CN115635212A

  • High-temperature-resistant elastic conductive silver paste and preparation method thereof

    CN116130143A

  • High-conductivity silver paste and preparation method thereof

    CN105632588A

  • Low-temperature conductive silver paste for main grid of photovoltaic HJT battery and preparation method of low-temperature conductive silver paste

    CN115274179A